2017
DOI: 10.1590/1413-812320172211.26352015
|View full text |Cite
|
Sign up to set email alerts
|

Sobrevida de pacientes com AIDS e coinfecção pelo bacilo da tuberculose nas regiões Sul e Sudeste do Brasil

Abstract: The study investigates the survival of patients with co-infection AIDS-TB through a retrospective study of a cohort of individuals aged 13 or more and the diagnosis of AIDS reported in the years 1998-99 and following 10 years. Of the 2,091 AIDS cases, 517 (24.7%) had positive diagnosis for tuberculosis, and 379 (73.3%) were male. The risk among co-infected patients was 1,65 times the not co-infected. Have been compared the exposed and non-exposed through the Kaplan-Meier and Cox method. The variables associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
5
0
6
Order By: Relevance
“…A linkage study between SIM and SINAN carried out with TB deaths in 2006 demonstrated 23.4% of under-reported cases in Paraná and 39.4% in Brazil (de Oliveira et al, 2012). A survey performed in Rio de Janeiro demonstrated even higher under-reporting rates, exceeding 40% (De Melo et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A linkage study between SIM and SINAN carried out with TB deaths in 2006 demonstrated 23.4% of under-reported cases in Paraná and 39.4% in Brazil (de Oliveira et al, 2012). A survey performed in Rio de Janeiro demonstrated even higher under-reporting rates, exceeding 40% (De Melo et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…In this system, when TB and HIV infection are present in the death certificate, the underlying cause of death is automatically defined as AIDS (Rocha et al, 2015). Considering that there are already studies that discuss the lethality of HIV/TB co-infection (De Melo et al, 2017), in the present study we opted to analyze the deaths by TB as underlying cause, i.e., HIVnegative individuals.…”
Section: Methodsmentioning
confidence: 99%
“…The considerable proportion of estimates of DALYs due to TB among HIV-positive individuals reinforces the epidemiological relevance of TB-HIV co-infection as a comorbidity of significant impact on public health in Brazil [ 41 , 42 ]. Currently, despite the improvements in the quality of management and care of TB in people living with HIV/AIDS and increased access to active antiretroviral therapy (ART) in Brazil, morbidity and mortality due to TB continues remains high among HIV-positive people in the country, impacting negatively the survival and quality of life of this population [ 43 ]. TB is the leading cause of death among infectious diseases defined in HIV/AIDS patients in the country [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brazil, in particular, has already recorded, since the first registered cases by the end of 2017, a total of 327,655 deaths had HIV/AIDS as the primary cause 5 . There has been a significant reduction in mortality in the country in recent years, mainly due to the availability of free access to diagnosis and treatment for HIV/AIDS by the Ministry of Health, starting in 1996 6,7 . The introduction of antiretroviral therapy (ART) has made it possible to improve the quality and survival of patients, since it reduces the incidence of opportunistic infections and positively regulates the immune system (increased TCD4+ lymphocyte count) of individuals affected by AIDS.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in the number of prevention and testing campaigns for individuals are factors that can increase the time between diagnosis and the start of drug intervention. In addition, in some cases, the scarcity of medication and difficulties related to adherence to treatment are still important factors related to disease progression 7,12 .…”
Section: Introductionmentioning
confidence: 99%